2005
DOI: 10.1007/s10591-005-4039-1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of mandated reporting among family therapists: a qualitative analysis

Abstract: Mandated reporting of child abuse by Family Therapists (FTs) has been examined by the authors in two previous studies. The first study found that mandated reporting issues negatively affected FTs' abilities to maintain a systemic focus. The second study surveyed types and frequencies of negative experiences of FTs with mandated reporting. A 46-item questionnaire was administered to 101 FTs. Results were significant for four of the items. The respondents also provided 116 comments related to mandated reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Such problems are compounded when there is little constructive feedback to help reporters of suspected abuse improve their reporting practices. 30,54,55 Appellate courts in the United States have upheld mandated reporting statutes on the presumption that reasonable suspicion is readily understood and interpreted by any person of common intelligence, [56][57][58][59][60][61] and that only "on occasion" do mandated reporters struggle to decide whether reasonable suspicion exists. 59 What the courts seem not to appreciate is that child abuse is often a possible explanation for a child's injuries or behavior: a toddler whose bruise has no clear etiology, an inexplicably angry 8-year-old, a kid who "says" he fell off his bike.…”
Section: Discussionmentioning
confidence: 99%
“…Such problems are compounded when there is little constructive feedback to help reporters of suspected abuse improve their reporting practices. 30,54,55 Appellate courts in the United States have upheld mandated reporting statutes on the presumption that reasonable suspicion is readily understood and interpreted by any person of common intelligence, [56][57][58][59][60][61] and that only "on occasion" do mandated reporters struggle to decide whether reasonable suspicion exists. 59 What the courts seem not to appreciate is that child abuse is often a possible explanation for a child's injuries or behavior: a toddler whose bruise has no clear etiology, an inexplicably angry 8-year-old, a kid who "says" he fell off his bike.…”
Section: Discussionmentioning
confidence: 99%
“…The companion article to this study provides a qualitative analysis of the written responses of the FTs to the survey instrument (Strozier et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that mandated reporting issues negatively affect family therapists' abilities to maintain a systemic focus (Strozier et al, 2005). Thus, it is important for family and couple therapists to remain aware not only of the mandated reporting laws in their practice jurisdiction but also the impact of reporting on the therapy relationship in order to competently protect and treat their clients.…”
Section: Exceptions To Confidentialitymentioning
confidence: 99%